Motor Performance Is not Enhanced by Daytime Naps in Older Adults - Backhaus, Winifried; Braass, Hanna; Renné, Thomas; Gerloff, Christian; Hummel, Friedhelm C. (Frontiers in Aging Neuroscience, 2016)
The impact of sleep on motor learning in the aging brain was investigated using an experimental diurnal nap setup. As the brain ages several components of learning as well as motor performance change. In addition, aging is also related to sleep architectural changes. This combination of slowed learning processes and impaired sleep behavior raises the question of whether sleep can enhance learning and specifically performance of procedural tasks in healthy, older adults. Previous research was able to show sleep-dependent consolidation overnight for numerous tasks in young adults. Some of these study findings can also be replicated for older adults. This study aims to clarify whether sleep-dependent consolidation can also be found during shorter periods of diurnal sleep. The impact of midday naps on motor consolidation was analyzed by comparing procedural learning using a sequence and a motor adaptation task, in a crossover fashion in healthy, non-sleep deprived, older adults randomly subjected to wake (45 min), short nap (10-20 min sleep) or long nap (50-70 min sleep) conditions. Older adults exhibited learning gains, these were not found to be sleep-dependent in either task. The results suggest that daytime naps do not have an impact on performance and motor learning in an aging population.